2019
DOI: 10.35513/21658005.2019.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the potential distribution of striped hyena Hyaena hyaena in Iran

Abstract: Predictive potential distribution modelling is crucial in outlining habitat usage and establishing conservation management priorities. Species distribution models estimate the relationship between species occurrences and environmental and spatial characteristics. Herein, we used maximum entropy distribution modelling (MaxEnt) for predicting the potential distribution of the striped hyena Hyaena hyaena in the entire country of Iran, using a number of occurrence records (i.e. 118) and environmental variables de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Although considered a habitat generalist, several studies have highlighted the strong dependence of the European badger on forests (Huck et al, 2008;Fabrizio et al, 2019), making it highly vulnerable to forest loss and habitat fragmentation. Also, striped hyaenas in Iran are constantly threatened by road vehicle collisions (Tourani et al, 2014;Mohammadi et al, 2018), habitat destruction and land modification (Dadashi-Jourdehi et al, 2020). Road construction and habitat fragmentation coupled with water scarcity and the aridity of landscapes further reduce the suitable habitats for certain wildlife species in Iran, especially the wild goat.…”
Section: Discussionmentioning
confidence: 99%
“…Although considered a habitat generalist, several studies have highlighted the strong dependence of the European badger on forests (Huck et al, 2008;Fabrizio et al, 2019), making it highly vulnerable to forest loss and habitat fragmentation. Also, striped hyaenas in Iran are constantly threatened by road vehicle collisions (Tourani et al, 2014;Mohammadi et al, 2018), habitat destruction and land modification (Dadashi-Jourdehi et al, 2020). Road construction and habitat fragmentation coupled with water scarcity and the aridity of landscapes further reduce the suitable habitats for certain wildlife species in Iran, especially the wild goat.…”
Section: Discussionmentioning
confidence: 99%
“…The striped hyaena occurs in Asia from the Indian subcontinent to the Levant (including 20 countries) and most parts of Africa except the southern part (including 18 countries) 27 , 28 . According to the IUCN Red List, the striped hyaena has been categorized as a near threatened species (NT), because of persecution (mainly poisoning the carrions) and decreasing domestic and natural carrions 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Striped hyaenas are one of the least studied large carnivores in Iran and there is limited data available on their habitat needs and spatial distribution. In Iran, the striped hyaena has a widespread distribution; however, its population has decreased severely 27 . The main causes are habitat loss and anthropogenic activities such as conversion of the natural grasslands to agricultural lands, poaching, poisoning the carrions, using organs for medicine and superstitious beliefs, and road collisions 27 , 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, it appears wildlife and domestic animals share strains, and in other cases the strains found in wildlife and dogs are quite different. 4,9 In 2020, Dadashi-Jourdehi et al 25 reported that the most suitable habitats for striped hyenas in Iran are mountainous areas in the north and west of the country as well as plain areas located in central and eastern Iran, but there is no report on the incidence of CDV for hyenas in Iran, and the conservation status of striped hyenas and the potential impact of the disease on the hyenas' population or other carnivores is unclear. So, more studies are needed to investigate the presence of the virus, the level of the infection in regional and Iranian hyenas populations, and the type of virus strains and how the virus remains in the wild.…”
Section: Discussionmentioning
confidence: 99%